Analysis of Fuel Consumption Variation of the 8dkm-28e Main Engine at Stable Performance of 620 RPM in the MV. Tanto Keluarga - Nourman Viqry Dwinanda; Agus Prawoto; Shofa Dai Robbi; Monika Retno Gunarti; Novitasari (International Journal of Science and Environment (IJSE), 2026)
This study examines the variation of Heavy Fuel Oil (HFO) fuel consumption of the DAIHATSU 8DKM28e Main Engine at a stable performance condition of 620 RPM on the container ship MV. Tanto Keluarga, amidst the pressure of increasing fuel costs and regulations on maritime efficiency and decarbonization. The study uses a descriptive quantitative approach with a population of all main engine operational data during a certain voyage period and a sample of 5 sheets of Noon Report At Sea at a stable voyage condition in the open sea. The main instrument is the daily noon report that records the main engine speed, turbocharger speed, fuel rack, HFO consumption, and weather and sea conditions, plus ship technical documents and academic literature as secondary instruments. The data analysis technique used is descriptive quantitative analysis, with the calculation of averages, ranges, and trends as well as simple correlation examinations between performance parameters. The results show that HFO consumption varies up to approximately 1,005 liters per day at a relatively stable RPM, with a pattern closely related to changes in fuel rack, turbocharger speed, and sea state and weather conditions. The findings support that the main engine performance condition at 620 RPM is in dynamic equilibrium, so that fuel efficiency assessment needs to integrate internal and external factors simultaneously to support operational management, OPEX reduction, and compatibility with IMO EEXI and CII regulations.